Haematology Of Gastrointestinal Helminths Affected Horses - P.V., Sonone; G.B., Srikhande; A.M., Rode; S.W., Kolte (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Present study was carried out to determine the incidence of gastrointestinal helminths in horses of Nagpur city. Among gastrointestinal helminths the order of helminth prevelence was Strongylus sp. (44.12%), Anoplocephala sp. (30.88%), Parascaris equorum (14.71%), mixed infection (Strongylus + Parascaris equorum) (5.88%) and lowest one was Gastrodiscus sp. (4.41%). Haematological study showed significant changes in haemoglobin, PCV, TEC and DLC in infected horses before and after treatment. Combination therapy proved to be highly effective against the gastrointestinal helminths.